Influence of Nitrogen Gas Flow Rate on The Microstructural and Mechanical Properties of Tin Deposited Carbon Steel Synthesized by Cae - A. Mubarak; E. Hamzah (ASEAN Journal on Science and Technology for Development, 2006)
This paper reports on the preparation of titanium nitride (TiN) thin films on carbon steel plates, using cathodic arc evaporation CAE PVD technique. We studied and discussed the effect of various nitrogen gas flow rates on microstructural and mechanical properties of TiN-coated carbon steel plates. The coating properties investigated in this work included the surface morphology, thickness of deposited coating, adhesion between the coating and substrate, coating composition, coating crystallography, hardness and surface characterization using a field emission scanning electron microscope (FE-SEM) with energy dispersive X-ray (EDX), Xray diffraction (XRD) with glazing incidence angle (GIA) technique, scratch tester, hardness testing machine, surface roughness tester and atomic force microscope (AFM). SEM analyses showed that all the films had columnar and dense structures with clearly defined substrate-film interfacial layers. The hardness of TiN-coated carbon steel was noted six times more than the hardness of uncoated one. An increase in nitrogen gas flow rate showed; decrease in the formation of macro-droplets, average roughness (Ra) and root-mean-square (RMS) values in CAE PVD technique. During XRD-GIA studies, it was observed that by increasing the nitrogen gas flow rate, the main peak [1,1,1] shifted toward the lower angular position. Microhardness of TiN-coated carbon steel showed about six times increase in hardness than the uncoated one. Scratch tester results showed an average adhesion between the coating material and substrate. Thanks to the high resolution power could be observed that by increasing nitrogen gas flow rate there was percentage increase in the bearing ratio while percentage decrease in histogram.